BIAS GENDER DALAM TINGKAT PENGEMBALIAN INVESTASI PENDIDIKAN DI SUMATERA BARAT - Melty Roza Adry; Selli Nelonda (Universitas Negeri Padang, 2016)
This study aims to estimate the rate of return of gender-based school in West Sumatra using Mincer earnings function. This study uses database KOR SUSENAS West Sumatra in 2012 for collecting data. The two-step Heckman model of ordinary least square (OLS) is used for data analysis. The findings of this study are as follows. First, return to schooling is higher for male than female, for both service and manufacturing industries. Second, years of schooling, years of schooling interaction with manufacturing industril, years of schooling interaction with in service industril, the squared years of schooling interaction with manufacturing industril, the squared years of schooling interaction with service industril, gender interaction with service industril, gender interaction with manufacturing industril and urban/rural location are significantly influence return to schooling. While, squared years of schooling is not significantly influence return to schooling. Keywords : Mincerian Earnings Function; Gender; Return on schooling, Two Step Heckman model.